A314 A CHARACTERIZATION OF NUTRITION STATUS AND GUT MICROBIOTA IN OBSESSIVE-COMPULSIVE DISORDER (OCD) IN YOUTH. (1st March 2018) - Macphail, E C; Reimer, R; Arnold, P D
Abstract: Background: Obsessive compulsive disorder (OCD) affects 5.2–10.4 million North Americans. Most commonly diagnosed in childhood and adolescence, it can result in years of struggle and has been listed among the top ten causes of disability by the World Health Organization. Zinc is physiologically essential and integral for optimal health; however, zinc deficiency is quite prevalent. Not only are youth (particularly females) more likely to have zinc deficiency risk factors, but they are also in a life stage where zinc deficiency is more problematic, based on its importance developmentally. Neural zinc levels have implications for neuroplasticity (a factor in cognitive flexibility, a feature of executive function that is impaired in OCD). Additionally, zinc supplementation has been demonstrated to improve mental health, and in animal models, zinc deficiency has been shown to alter the gut microbiota. Gut microbiota profiles have been linked to anxiety and depression (potentially due to interactions with the enteric nervous system). Given the high co-occurrence rates between these and OCD, as well as the fact that patients with OCD have been reported to have higher rates of gastrointestinal distress than controls, an investigation into nutrition and gut microbiota profiles in youth with OCD is a logical step. Aims: The aim of this study was to assess the role of zinc and of the gut microbiota in OCD in youth, and to determine any differences between youth with and without OCD. It was hypothesized that higher zinc intake and status, as well as greater gut microbial diversity, would be associated with greater cognitive flexibility and with decreased OCD symptom severity. It was also thought that youth with OCD would be more likely to have non-optimal nutrient intake/levels and dysregulation of gut microbiota than youth without OCD. Methods: Zinc status analysis was conducted via 3-day dietary record, serum levels, and hair levels. Berg's Card-Sorting Test and Trail-Making Tests A&B were used to assess cognitive flexibility; clinical interview and self-report scales measured anxiety, depression, and OCD symptoms; and gut microbiota was quantified via stool samples analyzed using qPCR and 16S sequencing. Data were compared for youth with OCD versus youth without OCD. Results: Commonalities among dietary intake patterns and nutrient status for youth with OCD, as well as their gut microbiota profiles in comparison to youth without OCD, will be discussed. Conclusions: Nutritional status' impact on mental health is underexplored, and no literature to date combines analysis of zinc, cognitive flexibility, and gut microbiota, particularly in OCD. This study's characterization of nutrient intake/status and gut microbiota has the potential to aid development of alternative therapies for youth with OCD. Funding Agencies: Ferring Canada, Branch-Out Neurological Foundation, Mathison Centre for Mental Health Research & Education